VD_FINDINFO APG 7/11 - 7/2012 vom 18. September 2012 - VD Tribunal cantonal (2012)
APG, RESTITUTIONEN GÉNÉRAL, PÉREMPTION | 1a al. 3 LAPG, 21 LAPG, 23 LAPG, 25 LPGA, 27 LPPCi, 28 LPPCi, 35 LPPCi, 36 LPPCi, 75 LPPCi, 7 OIPCC, 41 al. 3 OPCi